Minimization of Harmonics in BLDC Motor Drive Using Fuzzy Logic Based Variable Inductor Filter Drive - Chaudhari, Parag S.; Patil, Sanjaykumar L. (Australian journal of electrical & electronics engineering, 2020)
Harmonic analysis and its mitigation are very important for high-performance brushless DC motor drives. Conventional fixed LC filter work around its tuned frequency, resulting narrow band for operation. High-frequency current ripples can result in significant damage to the motor bearings. In this paper, afuzzy-based servo controlled variable inductor is proposed as apart of LC filter. Arotary variable inductor is controlled by using DC servo motor connected to it. Rotary variable inductor shaft is to be turned around to adistinct angle to attain imposed inductor value by using DC servomotor position control. This expands its operating frequency range more effectively. The current harmonics are compared for operation with and without the proposed filter. Proposed system was simulated using MATLAB/Simulink and implemented on 2 kW, 48 V, 8 pole pair BLDC motor drive for demonstration. Athree-phase IGBT-based voltage source inverter is used to drive the motor. Experimental results presented validate the effectiveness with improvement in current harmonics elimination by 22%. More importantly, improvement in THD is observed at lower operating frequencies too. This makes the scheme more useful for varying speed/load applications. Reduction in harmonics enhances other performance parameters of the BLDC motor drive.